EKSTRAK ANTOSIANIN DARI BUAH STROBERI (FRAGARIA X ANANASSA) SEBAGAI PENGGANTI EOSIN PADA JARINGAN HATI TIKUS DENGAN PEWARNAAN HEMATOXYLIN-EOSIN - Laila, Nazmy Noor; Mahmud, Dani; Oktari, Anita; Rukhiat, Diat (Universitas Cokroaminoto Palopo, 2025)
Tissue staining is necessary to show the structure and morphology of the tissue, namely Hematoxylin Eosin (H&E) staining. However, eosin is carcinogenic when used in the long term. The aim of this research is expected to develop the use of natural materials as an alternative for Hematoxylin-Eosin histological staining. One of the color pigments that can be obtained from natural materials is the anthocyanin pigment found in strawberries. The anthocyanin extract from strawberries, which is acidic like eosin, will bind to positively charged molecules in the basic cytoplasm. The design of this study uses a simple experimental design (Posttest Only Design). Based on the Mann Whitney U test, a significant result was obtained with a value of sig.<.001 <0.05, indicating a significant difference in the results between the preparations stained with hematoxylin and eosin and those stained with hematoxylin and anthocyanin extract. Thus, it can be concluded that statistically, staining with hematoxylin and anthocyanin extract cannot be used as a substitute for hematoxylin eosin. Nevertheless, the results of staining the preparations using hematoxylin and anthocyanin extract still produce color in the cytoplasm, and are sufficiently contrasting to distinguish between the color of the cytoplasm and the color of the nucleus.